Characteristics and driving mechanisms of species beta diversity in desert plant communities. - Lamei Jiang; Guanghui Lv; Yanming Gong; Yan Li; Hengfang Wang; Deyan Wu (PLoS ONE)
Species dissimilarity (beta diversity) primarily reflects the spatio-temporal changes in the species composition of a plant community. The correlations between β diversity and environmental factors and spatial distance can be used to explain the magnitudes of environmental filtering and dispersal. However, little is known about the relative roles and importance of neutral and niche-related factors in the assemblage of plant communities with different life forms in deserts. We found that in desert ecosystems, the β diversity of herbaceous plants was the highest, followed by that of shrubs and trees. The changes in the β diversity of herbs and shrubs had stronger correlations with the environment, indicating that community aggregation was strongly affected by niche processes. The soil water content and salt content were the key environmental factors affecting species distributions of the herb and shrub layers, respectively. Spatial distance explained a larger amount of the variation in tree composition, indicating that dispersal limitation was the main factor affecting the construction of the tree layer community. The results suggest that different life forms may determine the association between organisms and the environment. These findings suggest that the spatial patterns of plant community species in the Ebinur Lake desert ecosystem are the result of the combined effects of environmental filtering and dispersal limitation.